If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 1) = 2(x + -3) + -1(1 + -2x) Reorder the terms: 4(1 + x) = 2(x + -3) + -1(1 + -2x) (1 * 4 + x * 4) = 2(x + -3) + -1(1 + -2x) (4 + 4x) = 2(x + -3) + -1(1 + -2x) Reorder the terms: 4 + 4x = 2(-3 + x) + -1(1 + -2x) 4 + 4x = (-3 * 2 + x * 2) + -1(1 + -2x) 4 + 4x = (-6 + 2x) + -1(1 + -2x) 4 + 4x = -6 + 2x + (1 * -1 + -2x * -1) 4 + 4x = -6 + 2x + (-1 + 2x) Reorder the terms: 4 + 4x = -6 + -1 + 2x + 2x Combine like terms: -6 + -1 = -7 4 + 4x = -7 + 2x + 2x Combine like terms: 2x + 2x = 4x 4 + 4x = -7 + 4x Add '-4x' to each side of the equation. 4 + 4x + -4x = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + 0 = -7 + 4x + -4x 4 = -7 + 4x + -4x Combine like terms: 4x + -4x = 0 4 = -7 + 0 4 = -7 Solving 4 = -7 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -25+7+11=35 | | -42+s=-46 | | A=-25 | | 7x-6(x+4)=-114 | | 4m+14-2m= | | -3.5y=-50 | | 7x+24=2x-6 | | 4.5-2.6+x=9 | | -9b+13-12=10 | | 75n=30 | | -4(x-2)=-40 | | 25+4-6=12 | | 3x-40=6x-10 | | 46-12+6=12 | | 4+3-5=7 | | 3+4(X+4)=27 | | 9x^2+36x+14=0 | | R+(-1.5)=-3.4 | | 18u(8)w(8)+30u(6)w(5)y(4)= | | 11x-2=x | | -15+8-14=35 | | 4-3+5=7 | | 3(7x-7)+13x= | | 4500+(4*x)+600=10,500 | | 11-(3x-6)+2(2x+5)-x= | | 4x+14-6=7 | | 45+16-2=14 | | (3*1500)+(4*x)+(3*200)=10,500 | | 0.4m-3= -1 | | 3x-5(x-5)=-6+3+21 | | 6+12+3=39 | | 45-16+2=14 |